1989
DOI: 10.1007/bf01852163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hypoxia on mitochondrial function and energy status in CCl4-induced cirrhotic rat liver

Abstract: The influence of hypoxia on hepatic mitochondrial function and energy status was studied in normal and carbon tetrachloride (CCl4)-induced cirrhotic rats. Under hypoxemia of 50 mm Hg-PaO2, hepatic energy status was suppressed both in normal and cirrhotic rats. After the reversal of hypoxia, it was completely restored in normal rats concomitant with a rapid elevation of hepatic mitochondrial redox state (overshoot phenomenon) and increase in the mitochondrial oxidative phosphorylative activity. By contrast, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Rather, these studies showed that cirrhosis disturbs cell redox states, as measured from increased cytoplasmic lactate:pyruvate ratios 30 and decreased acetoacetate/b-hydroxybutyrate ratios. 28,30 We also found other metabolic changes in cirrhosis that may not be directly related to hypoxia. There was a significant decrease of 40% observed in the NAD levels of cirrhotic rats, when expressed as a percentage of total phosphorus content.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Rather, these studies showed that cirrhosis disturbs cell redox states, as measured from increased cytoplasmic lactate:pyruvate ratios 30 and decreased acetoacetate/b-hydroxybutyrate ratios. 28,30 We also found other metabolic changes in cirrhosis that may not be directly related to hypoxia. There was a significant decrease of 40% observed in the NAD levels of cirrhotic rats, when expressed as a percentage of total phosphorus content.…”
Section: Discussionmentioning
confidence: 55%
“…These results are supported by previous reports that CCl 4 -induced cirrhotic rats showed decreases in hepatic ATP, ATP:ADP ratio and energy charge levels. 28,29 Experimental hypoxia in perfused rat livers resulted in decreased ATP levels, increased ADP and P i levels, and a 50% reduction in ATP:ADP ratios. 6,17 NMR studies in humans have also shown diminished ATP and an increased P i :ATP ratio in the cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of cirrhosis, hepatic mitochondrial function has been shown to be impaired as evidenced by reduced hepatic energy charge [1, 2, 3]and decreased rates of ATP production [4]. Hepatic mitochondrial function has also been indirectly assessed in humans by measuring the arterial ketone body ratio (AKBR) which reflects mitochondrial NAD + /NADH ratio and energy state.…”
Section: Introductionmentioning
confidence: 99%